Analisis Optimalisasi Capaian Akademik MuridKelas X melalui Implementasi Strategi Project-Based Learning pada Bidang Studi Pendidikan Pancasila dan Kewarganegaraan (PPKn) - Amalya, Cici Syaidatun; Silvia, Novi; Nasution, Rahmad Santoso; Adi, Panggi Nur (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2026)
This study evaluates the impact of Project-Based Learning (PjBL) on the academic performance of Grade X-5 students at SMA Negeri 1 Rantau Selatan in Civic Education (PPKn). Conducted as action research involving 36 participants, the observation followed three systematic phases. Data revealed a significant surge: the initial average of 68.36 (38.89% proficiency) rose to 75.29 in Cycle I, peaking at 81.61 with a 91.67% proficiency rate by Cycle II. These findings confirm that PjBL effectively drives consistent academic improvement. While most students demonstrated positive progress, intensive guidance remains essential for those yet to meet the required standards. Consequently, this research recommends the sustained integration of PjBL, paired with instructional strategy adjustments, to ensure all students reach optimal learning competency. Keywords: Project-Based Learning (PjBL), Learning Achievement, Pancasila and Citizenship